THE IMPACT OF THE CHANGE IN THE MUSICAL ATTRIBUTES OF THE CODE OF POINTS (2013-2016) ON THE ROUTINES IN RHYTHMIC GYMNASTICS OF THE RIO 2016 OLYMPIC GAMES - Eliana Toledo; Mateus Oliveira; Maria Letícia Scarabelim; Bianca Assumpção (University of Ljubljana Press (Založba Univerze v Ljubljani), 2018)
The Rhythmic Gymnastics Code of Points, 2013-2016, was a milestone by allowing vocal music in routines. This study aimed to analyze the impact of this change in the routines, at the RIO 2016 Olympic Games. This is a documentary research, with two types of sources: official International  Federation  of  Gymnastics;  and  videos  of  the  routines.  The  sample  was composed of 26 individual athletes and 14 teams. The analysis was quantitative (incidence parameter) and qualitative (type of music). As a result, we identified that, of the 104 songs of individual routines, 81 were instrumental music (IM) and 23 represented music with voice and words (MVW). Among the IM, 21 were North-American (NA) and 60 from other nationalities (ON). Of the MVW, 11 were NA and 12, from ON. In team routines, of the 28 songs, 17 were IM and 11 were MVW. Of the IM, 6 were NA and 11, from ON. Among the MVW, 6 were NA and 5, from ON. We conclude that most of the gymnasts and teams used this new rule of the Code of Points. This change was effectively incorporated into world prominence delegations, and we verified the strong influence of NA music.